OP0173 How Much of A Barrier Is Excess Weight and Smoking for Achieving Sustained Remission in Early RA? Results from The Canadian Early Arthritis Cohort. (15th July 2016) - Bartlett, S.J.; Schieir, O.; Schulman, E.; Goodman, S.M.; Zhang, M.; Lin, D.; Andersen, K.M.; Boire, G.; Haraoui, B.; Hitchon, C.; Jamal, S.; Keystone, E.; et al.
Abstract : Background: Relatively little is known about whether and to what extent modifiable lifestyle factors such as excess weight and smoking impact the likelihood of achieving sustained remission (SR). Objectives: To explore the independent and combined effects of excess weight and smoking on achieving SR in early RA. Methods: We examined the first 3 years of data of ERA patients enrolled in the Canadian Early Arthritis Cohort (CATCH), a multicenter prospective cohort study. Participants met 1987 or 2010 ACR/EULAR criteria for RA, had <12 months of symptom duration, were not in remission at entry, and had BMI and at least 2 consecutive DAS28 scores available. SR was defined as DAS28<2.6 at two consecutive visits. Independent effects of BMI class (normal weight: 18.5–24.9, overweight: 25–2.9, obese: 30+) and smoking on time to SR were estimated using Cox proportional hazards, adjusting for age, sex, ethnicity, education, comorbidities, smoking (current, former/never), symptom duration, disease activity, and treatment. Potential joint effects of smoking and weight class were tested using an interaction in the model. Higher order interactions with other covariates were also examined. Results: The sample included 1, 008 patients with a mean (SD) age of 53 (15), symptom duration of 5 (3) months, DAS28 of 5.3 (1.3); 728 (72%) were female and 813 (81%) were white. Among males, 131 (47%) were overweight, 93 (33%) obese, and 55 (20%) smoked. Among females, 220 (30%) were overweight, 241 (33%) obese, and 109 (15%) smoked. At entry, 741 (74%) patients were treated with MTX (mono or combination therapy), relatively few 28 (3%) with a biologic, and 522 (52%) with steroids. The proportion in SR rose steadily; at 3 years 408 (38%) had achieved SR with a median (IQR) time to SR of 11.3 (11.2) months. In fully adjusted Cox survival analyses, BMI class (p=0.003) and smoking (p=0.046) were significantly associated with SR, as was a 3-way interaction for BMI class, smoking, and gender (p=0.02). Figure 1 depicts the combined impact of smoking and BMI class on the probability of achieving SR in a prototypical male and female patient: 53-years old, white, with some postsecondary education, 5 months symptom duration, 2 comorbidities, DAS28 of 5, and initial treatment with MTX and steroids. A non-smoking male with a healthy BMI and these characteristics would have a 41% probability of achieving SR within 3 years vs. only 15% for an obese male smoker. A non-smoking female with a healthy BMI and these characteristics would have a 27% probability of achieving SR within 3 years vs. only 10% for an obese female smoker. Conclusions: In this large "real-world" early RA cohort, two potentially modifiable lifestyle factors – smoking and excess weight – were prevalent and had significant independent and combined effects on the likelihood of achieving SR. Disclosure of Interest: None declared